2001
DOI: 10.1046/j.1365-2036.2001.01015.x
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide 24‐h prophylaxis in patients at high risk for post‐ERCP pancreatitis: results of a multicenter, randomized, controlled trial

Abstract: The main questions still debated relating to the diagnostic and therapeutic endoscopic procedures involving Vater's papilla (ERCP) are post-procedure pancreatitis and its prevention. Acute post-ERCP pancreatitis is still the most frequent and feared complication. A recent review of prospective series found a mean prevalence of 5.2% after diagnostic procedures and 4.1% after therapeutic procedures. 1 However, in recent prospective studies in non-selected cases the rate of this complication has been reported to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 29 publications
0
23
0
2
Order By: Relevance
“…Milewski et al confirmed that N-acetylcysteine was ineffective [40]. Two groups conducted an RCT and claimed that octreotide prevented post-ERCP pancreatitis [41,42], but two groups previously showed that octreotide was ineffective [48,49], corroborating negative findings of a meta-analysis of 10 other clinical trials [50]. The variable results of the octreotide studies are likely due to marked differences among the studies such as drug dose and duration, population, endpoints, etc.…”
Section: Chemoprevention Of Post-ercp Pancreatitismentioning
confidence: 54%
“…Milewski et al confirmed that N-acetylcysteine was ineffective [40]. Two groups conducted an RCT and claimed that octreotide prevented post-ERCP pancreatitis [41,42], but two groups previously showed that octreotide was ineffective [48,49], corroborating negative findings of a meta-analysis of 10 other clinical trials [50]. The variable results of the octreotide studies are likely due to marked differences among the studies such as drug dose and duration, population, endpoints, etc.…”
Section: Chemoprevention Of Post-ercp Pancreatitismentioning
confidence: 54%
“…Pharmacologic agents directed at decreasing pancreatic secretions, including histamine-2 receptor antagonists and octreotide, antiprotease therapies such as aprotinin and gabexate mesylate, and platelet-activating factor antagonists such as lexipafant, have not proven effective in improving important clinical outcomes [5,6,7,8]. Adequate analgesia, monitoring for complications and aggressive intravenous fluid resuscitation remain the hallmarks of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In the clinical setting recent randomized controlled trials have failed to demonstrate beneficial effects of octreotide pretreatment in the prevention of post-ERCPinduced pancreatitis [22,23]. In fact, according to the findings of the present study, it might actually be harmful to pretreat patients with octreotide prior to ERCP because should they develop pancreatitis it may be more severe.…”
Section: Discussionmentioning
confidence: 58%